When governments promise to prioritize public debt: Do markets care? - Mitu Gulati; Ugo Panizza; W. Mark C. Weidemaier; Gracie Willingham (Graduate Institute of International and Development Studies, 2019)
During the European sovereign debt crisis of 2011-13, some nations faced with rising borrowing costs adopted commitments to treat bondholders as priority claimants. That is, if there was a shortage of funds, bondholders would be paid first. In this article, we analyze the prevalence and variety of these types of commitments and ask whether they impact borrowing costs. We examine a widely-touted reform at the height of the Euro sovereign debt crisis in 2011, in which Spain enshrined in its constitution a strong commitment to give absolute priority to public debt claimants. We find no evidence that this reform had any impact on Spanish sovereign bond yields. By contrast, our examination of the U.S. Commonwealth of Puerto Rico suggests that constitutional priority promises can have an impact, at least where the borrower government is subject to supervening law and legal institutions.
Keywords: E62; H62; H63; P16; 330; Sovereign Debt; Debt Sustainability; Sovereign Spreads